(untitled) (Cadernos de Sociomuseologia, 2010)
For a long time, museum’s form and function were impregnated with social exclusion, only accessible for a prosperous and educated minority. It held the monopoly on the past and therefore in a way on the present and the future. However times have changed and different perspectives on museum practices have been taken. In 1989 the British Peter Vergo mentioned as quoted below, a number of possible museologies, including a ‘new’, and therefore presumably an ‘old’ type of museology: “At the simplest level I would define it, as a state of widespread dissatisfaction with the ‘old’ museology, both within and outside the museum profession; and though the reader may object that such a definition is not merely negative, but circular, I would retort that what is wrong with the ‘old’ museology is that it is too much about museum methods, and too little about purposes of museums; that museology has in the past only frequently been seen, if it has been seen at all, as a theoretical and humanistic discipline.” (Vergo, 1989)